3D QSAR of Pyrrolo Pyrimidine and Thieno Pyrimidines as Human Thymidylate Synthase Inhibitors. Issue 4 (2012) - Kumari, K. Meena; Yamini, L.; Vijjulatha, M.
Abstract : Thymidylate synthase (TS) is a crucial enzyme for DNA biosynthesis and many nonclassical lipophilic antifolates targeting this enzyme are quite efficient and encouraging as antitumor drugs. We report 3D-QSAR analyses on pyrrolo pyrimidine and thieno pyrimidine antifolates to contemplate the mechanism of action and structure-activity relationship of these molecules. By applying leave-one-out (LOO) cross-validation study, cross-validated q 2 value of 0.523 and 0.566 for CoMFA Ligand based (LB) and Receptor based (RB), 0.516 and 0.471 for CoMSIA LB and RB respectively. while the non-cross-validated r 2 values were found to be 0.974 and 0.969 for CoMFA LB and RB, 0.983 and 0.972 for CoMSIA LB and RB respectively. The models were graphically interpreted using CoMFA and CoMSIA contour plots. The results obtained from this study were used for rational design of potent inhibitors against thymidylate synthase.